Impact of altered WNT2B expression on bladder wall fibroblasts: implications for apoptosis regulation in the stroma of the lower urinary tract - Worst, Thomas; Daskalova, Kristina; Steidler, Annette; Berner-Leischner, Karin; Röth, Ralph; Niesler, Beate; Kriegmair, Maximilian; Erben, Philipp; Pfalzgraf, Daniel Philipp (Urologia internationalis, 2017)
Background: Little is known about the role of WNT signalling in pathological processes involving the urinary tract stroma. Here the impact of WNT signalling on bladder wall fibroblasts (BWFs) was studied using integrated expression profiling. Material and Methods: WNT ligand and downstream WNT pathway component expression was profiled in human BWFs using qRT-PCR. Highly expressed WNT2B was knocked down using siRNA in BWFs. The expression of 730 mRNAs and 800 miRNAs was analyzed on the nCounter MAX platform in #WNT2B and control transfected BWFs. qRT-PCR was used for validation in vitro and in matched scar and healthy bladder wall tissue samples of 12 patients with vesico-urethral anastomotic stricture (VUAS). Results: Thirteen genes and 9 miRNAs showed differential expression in #WNT2B cells. Among these were TNFSF10, a key apoptosis inductor, (0.22fold, p = 0.011) and miR-1246 (36.2fold, p = 0.031). miRNA target prediction indicated TNFSF10 to be regulated by miR-1246. qRT-PCR analysis confirmed differential expression of miR-1246 and TNFSF10 in #WNT2B BWFs. Furthermore, TNFSF10 was significantly underexpressed in VUAS tissue (p = 0.009). Conclusion: Perturbation of WNT signalling results in an altered expression of the apoptosis inductor TNFSF10. Similar changes are observed in VUAS. Further studies investigating the crosslink between WNT signalling and apoptosis regulation in the urinary tract stroma are warranted.
Gesehen am 09.05.2018